Cannulation-related wound complications after extra corporeal life support: A retrospective cohort study in a Dutch intensive care unit - Ineke van de Pol; Margreet van Rees; Gwen van Gool; Dewi Stalpers; Lisette Schoonhoven; Peter Noordzij; Erik Scholten (PLoS ONE, 2025)
Extracorporeal life support (ECLS) is a high-risk therapy for acute cardiac or respiratory failure. After weaning, wound healing at the cannulation site is often disrupted, leading to discomfort, delayed recovery, increased nursing workload, and higher costs. Available data on this issue is limited. This study describes the epidemiology of cannulation-related wound complications (CRWCs) in ECLS patients, defined as impaired wound healing at the cannulation site >72 hours after decannulation. A retrospective, single-center cohort study was conducted in the Intensive Care Unit of St. Antonius Hospital in the Netherlands. Between 2018 and 2023, successfully weaned ECLS patients treated with venovenous (VV) or venoarterial (VA) ECLS for more than 24 hours were included. Descriptive statistics were used to describe the incidence and characteristics of CRWCs. Risk factors for CRWCs were assessed using univariate logistic regression at the patient and insertion-site levels. A total of 73 patients were included in this study, of whom 33 (45%) had 37 CRWCs. CRWCs were characterized by fluid leaks (90%), wound dehiscence (70%), tissue necrosis (76%), and/or wound infection (49%). CRWCs were primarily located at the groin and the first signs appeared after seven days (IQR 5–9 days). Identified risk factors included increased age, lower BMI, lower nadir serum albumin, VA cannulation, surgical insertion, and dual cannulation. Wound healing was still incomplete in 17 (51%) patients at the time of hospital discharge. CRWCs occur in nearly half of all successfully weaned VV and VA ECLS patients, mostly at the groin. Due to the severity of the patient’s illness and the acute clinical setting, the identified risk factors cannot always be avoided. This study raises awareness, aiding in the early and better identification of at-risk patients and recognizing a CRWCs as a serious complication as early as possible.